Fungitoxic potential of aromatic rice against Pyricularia grise - MANASI MISHRA, S.N. TEWARI* and (Indian Phytopathology, 2003)
The utility of diverse botanical resources attracted the research workers to examine antimicrobial role against human and plant diseases. While exploring the fungitoxic potential of natural plant products, certain aromatic rice exhibited fungitoxicity against the blast pathogen, Pyricularia grisea Sacc. and the results are presented here.